DARI KARTINI HINGGA AYU UTAMI: MEMPOSISIKAN PENULIS PEREMPUAN DALAM SEJARAH SASTRA INDONESIA - -, Nurhadi (Diksi, 2007)
There has been an interesting phenomenon beginning late in the 20stcentury and lasting until early in the 21 century in Indonesian literary history: thegreat number of women writers suddenly producing literary works. In denial of theidea that it has been a phenomenon occurring all of a sudden, there has been aprecedent that could not be ignored: the number of Indonesian women writerscoming into activity far before the 1920s, the period becoming a milestonemarking the start of modern Indonesian literature, itself resulting from an impactof Western acculturation. The impact appeared first in the person named Kartini, awoman writer of some renown, whose achievement in the literary world is oftenunmentioned. The absence of women writers in the past from lists of knownwriters was often related to activities of placing their role on the sidelines by, forexample, not categorizing them writers of literary works or writers of qualityliterature (they being considered merely writers of popular literature) orcategorizing them merely happy-go-lucky writers and not the mainrepresentatives of their generation of writers. One may wonder whether the recentacknowledgement of Ayu Utami in Angkatan 2000 Sastra Indonesia as a pioneerin novel writing has been one of the strategies to bring about something contrary towhat has happened to those women writers in the past. It seems that the recentemergence of the aforementioned great number of women writers has not beenautomatically related to the efforts made by the feminist movement. A writer whohas made efforts for the sake of Kartini's fate is a male writer: Pramudya AnantaToer.Keywords : women writers, feminism, Indonesian literary history, role ofhistorical writing